Mejora del proceso de pegado de cartón en las empacadoras de banano del cantón Quevedo, provincia de Los Ríos, año 2013 - Álvarez Yépez, José Luis (2015)
The study for improving the bonding process was carried out in cardboard packing banana Quevedo Canton during the years 2013 and 2014. The specific objectives of this research were to examine the current situation of the process of gluing cardboard baler’s banana, determine levels of productivity in the process of gluing cardboard balers banana, make time study in the process of gluing cardboard, a technical study to improve the process of gluing cardboard balers banana and establish the profitability of the investigation. The investigation resulted in the construction and implementation of a semiautomatic machine for carton gluing process shows profitability and productivity, investment has a ratio of 1.11 cost-benefit and payback period on investment of 1.22 years, so that makes feasible the implementation team. Regarding the technical study, research indicated that the standard time of the manual process cartons bonding process to semi dropped from 122 seconds to 55.2 seconds, which means a decrease of 54.75% in addition to the process in the semiautomatic machine flow carton gluing process is divided into three activities: Select pile cardboard, place the cardboard gluer machine and carton pick up and carry the dockside. The design and implementation of the semiautomatic machine for the gluing process cartons of bananas in the packing has an investment amounting to $ 1,944.41.